Analysis and Formulation of Deception Capabilities against Monopulse Tracking Systems - S. Aziz, Jabir (Journal of Engineering and Sustainable Development, 2006)
Monopulse technique is the most common used technique in the tracking systems because it has the ability to obtain complete angle-error information on a single pulse. For one target, the antenna boresight of the monopulse tracking system will track the target while for two targets (or more), the antenna boresight will tracks the direction of the center of energy that transmitted or reflected by these targets. This paper introduces the analysis of this phenomena and how to utilize it to deceive angularly the monopulse tracking system. This analysis consists of the direction determination of the center of energy transmitted (or reflected) by the two targets before reaching the resolution angle, then the correction in the direction toward one of these targets after the resolution angle. The optimum separation between the two targets for deception has been calculated. The results of this analysis and calculation show that, there is an acceptable miss distance from the target when the distance between the two targets was selected to be anoptimum distance.